Analisis Penerapan Metode User Centered Design dengan pengujian metode Cognitive Walkthrough - Haezrah Oktavini; Reni Aryani; Edi Saputra; Ulfa Khaira (Jurnal PROCESSOR, 2024)
The Siginjei Jambi Museum is one of 439 museums in Indonesia which stores and exhibits various collections of historical relics and civilizations from the past and is real evidence of history that has occurred so it is worthy of being used as a source of learning and tourist visits. The management of the Siginjei Jambi Museum is still a traditional museum, so the Siginjei Jambi Museum needs to innovate by implementing information technology in the form of an e-museum or website to increase the number of visitors and can be accessed quickly without space and time constraints. Interface design is an important thing that needs to be considered before creating a website so that the website created can meet user needs. The researcher created the interface design for the E-Museum Siginjei Jambi website using the user centered design method because with this method the interface design is designed based on user input. The results of testing the design that was created using the cognitive walkthrough method with a total of 5 respondents were learnability 97.7%, error 1.77%, and efficiency 94.3%.